The Centralia Tragedy of 1919: Elmer Smith and the Wobblies - McCallum, Todd (Labour / Le Travail, 1995)
The article reviews the book, "The Centralia Tragedy of 1919: Elmer Smith and the Wobblies," by Tom Copeland.
Keywords: BOOKS – Reviews; CENTRALIA Tragedy of 1919: Elmer Smith & the Wobblies; The (Book); COPELAND; Tom; Lawyers; Nonfiction